Effects of vaccinia virus anti-inflammatory protein 35K and TIMP-1 gene transfers on vein graft stenosis in rabbits. - Puhakka, H; Turunen, P; Gruchala, M; Bursill, C; Heikura, T; Vajanto, I; Greaves, D; Channons, K; Ylä-Herttuala, S (2005)
BACKGROUND: Vein graft stenosis is a common problem after bypass surgery. Vein grafts are ideal targets for gene therapy because transduction can be made ex vivo before grafting. Since chemokines and inflammatory factors are involved in vein graft thickening, we tested a hypothesis that the vaccinia virus anti-inflammatory protein 35K which can sequester CC-chemokines, can reduce vein graft thickening in vivo. MATERIALS AND METHODS: We used adenovirus-mediated gene transfer (1x10(9) pfu/ml) of 35K and compared its effects on reducing stenosis in a rabbit jugular vein graft model with tissue inhibitor of metalloproteinase-1 (TIMP-1) and LacZ control gene. TIMP-1 was used in this study because it has previously been shown to inhibit vein graft stenosis in other model systems. The expression of transgenes in the transduced segments was confirmed by RT-PCR. Vein grafts were analyzed using immunohistological and morphometric methods at the three-day time-point and at two-week and four-week time-points. RESULTS: It was found that the anti-inflammatory protein 35K was an efficient factor in reducing neointima formation at the two-week time-point, indicating that inflammatory factors play an important role in vein graft stenosis. At the four-week time-point, 35K still showed a reduced accumulation of macrophages. TIMP-1 also tended to reduce neointimal thickening at the two-week time-point as compared to LacZ. CONCLUSION: It was found that 35K is an efficient factor in reducing neointima formation, macrophage accumulation and proliferation in rabbit vein grafts after adenoviral ex vivo gene transfer.